KEBIJAKAN PEMERINTAH JEPANG DALAM MENINGKATKAN JUMLAH WISATAWAN MUSLIM ASIA TENGGARA PADA ERA PM SHINZO ABE - Hamidah, Siti (Ministry Of Tourism, 2017)
Achieving the award for World's Best Non-OIC Emerging Halal Destination at the World Halal Tourism Awards (WHTA) 2016 in Abu Dhabi, United Arab Emirates is a remarkable achievement for Japan. This award delivers a positive perception of Muslim tourists from other countries that Japan has transformed into a Muslim-friendly country. This research aims to illustrate the profile of Japanese tourism, knowing the key to Japan's success in increasing the number of Southeast Asian tourists, and providing recommendations to the Government of Indonesia. The research applies qualitative method by using descriptive data analysis technique. This study uses secondary data consisting of previous researches such as books, articles of national and international journals, theses, writings on the internet that can be accounted for, as well as interviews with Muslim tourists who have visited Japan as primary data. The results show that Japan's strategy to increase Southeast Asian tourists is through the Tourism-oriented Country Policy (2013) and New Tourism Strategy to Invigorate the Japanese Economy (2016). Referring to the success of Japan, this study recommends the Government of Indonesia to perform institutional strengthening especially from the aspects of policy and its implementation by relevant stakeholders, halal certification, tourism destination development, and promotions.